PEMBERIAN BEBERAPA DOSIS TEPUNG BIJI PINANG (Areca catechu L.) LOKAL RIAU UNTUK MENGENDALIKAN HAMA KEONG EMAS (Pomacea canaliculata L.) PADA TANAMAN PADI - Laoh, Hennie; Rustam, Rusli; Permana, Riadi (PEST Tropical Journal, 2013)
Rice is an important food in Indonesia, because it is the staple food for mostpeople. Golden snail (Pomacea canaliculata L.) is an important pest in rice plant.Synthetic chemical pesticides control has many negative impacts such as theoccurrence of pest resistance, pest resurgence and environmental pollution. Theuse of betel nut (Areca catechu L.) as a molluscicides is one of alternative pestcontrol to reduce the use of synthetic chemical pesticides. The purpose of thisstudy is to obtain the exact dose of betel nut flour to control golden snails(Pomacea canaliculata L.) in rice plants. The research was conducted atLaboratory of Plant Pest and Unit Pelaksana Teknis (UPT) Kebun PercobaanFakultas Pertanian Universitas Riau by using a completely randomized designwith 5 treatments and 4 replications. Treatment consists of betel nut flour dose of4 g/clump, 5 g/clump, 6 g/clump, 7 g/clump and 8 g/clump. Doses of betel nutflour 8 g/clump able to control golden snail with a total mortality of 87.49%.Appropriate dose to kill 95% golden snail is 1% or the equivalent of 10 g/clump.Keyword: Rice (Oryza sativa L.), Golden Snail (Pomacea canaliculata L.),Betel nut (Areca catechu L.)